Round length optimisation for P2P network gaming - Webb, Steven; Soh, Sieteng (Curtin University, 2007)
The Referee Anti-Cheat Scheme (RACS) increases the scalability of Client/Server (C/S) games by allowing clients to exchange updates directly. Further, RACS maintains the security of C/S as the trusted referee (running on the server) is the game authority, simulating all client updates to validate the simulation. In RACS time is divided into rounds, and every player generates one update per round. The round length d is bounded by dmax which is specified by the game developer. The referee may reduce d to increase game responsiveness for players. Existing approaches to adjust d require purely distributed algorithms as they do not have a trusted central authority. These algorithms are slow and use considerable bandwidth. In this paper we propose a delay model for RACS, and two centralised algorithms to calculate d for maximum responsiveness - an optimal brute force approach and an efficient voting algorithm. We use simulation to show that the voting algorithm produces nearly optimal results, and analytical analysis to show that its processing requirements are far lower than the brute force approach.